Emerging Technologies to Create Inducible and Genetically Defined Porcine Cancer Models - Schook, Lawrence B.; Rund, Laurie; Begnini, Karine R.; Remião, Mariana H.; Seixas, Fabiana K.; Collares, Tiago (Frontiers in Genetics, 2016)
There is an emerging need for new animal models that address unmet translational cancer research requirements. Transgenic porcine models provide an exceptional opportunity due to their genetic, anatomic, and physiological similarities with humans. Due to recent advances in the sequencing of domestic animal genomes and the development of new organism cloning technologies, it is now very feasible to utilize pigs as a malleable species, with similar anatomic and physiological features with humans, in which to develop cancer models. In this review, we discuss genetic modification technologies successfully used to produce porcine biomedical models, in particular the Cre-loxP System as well as major advances and perspectives the CRISPR/Cas9 System. Recent advancements in porcine tumor modeling and genome editing will bring porcine models to the forefront of translational cancer research.